Implementasi SAMSAT Delivery Service dalam Meningkatkan Kualitas Pelayanan Publik - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; PUTU ADITYA FERDIAN ARIAWANTARA (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
Public administration have important task to provide public services in any sectors, to collect taxes from citizens, and other services to fulfill any citizens needed based on institutional law. Based on the values that make it easy for citizens in paying taxes, then the paradigm shift that emerged in the era of bureaucratic reform, particularly in order to improve the quality of public services in Indonesia is "bureaucrats should be able to serve", not to "receive services from the citizen ". To implementing the public services, SAMSAT East Java Province tried to made a new benchmarking strategy to increase the quality of public services itself. It called SAMSAT Delivery Service to made an easy way to collect automotive tax from citizens. SAMSAT Delivery Service is a breakthrough in service tax payment vehicle, which uses the values applied by the ministry in the private sector.This service is one of many superior service in SAMSAT East Java Province and an example project of public administration operational task in Indonesia.